Repensando el marco de la FIFA para la protección de menores - Ripoll González, Enric (2026)
The Fédération Internationale de Football Association’s current regulations on the international transfer of minors, though intended to protectyoung players, often fail to achieve that purpose. For that reason, framed within the principles of sports autonomy and respect for European law, the authors propose the FIFA Minors License, an annual certification system imposed on clubs to ensure adequate education, accommodation, and training of the children. Its main advantages are shifting responsibility to the hosting club enabling continuous monitoring, avoiding regulatory loopholes, reinforcing FIFA’s role in safeguarding children’s rights in football and providing stronger guarantees for minors’ welfare.